(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The paper presents the place of traditional library in higher education in a digital age. In nations of the world, educational system is now digital but notwithstanding traditional library still have a place in our educational system. The paper presents the History of Libranries; it further examined the concept of Traditional Library, this helps to reveal what traditional library entails. The paper concluded by looking into the place of Traditional Library in Higher Education in 21st Century.